2021
DOI: 10.1371/journal.pone.0244747
|View full text |Cite
|
Sign up to set email alerts
|

Using Fitbit data to examine factors that affect daily activity levels of college students

Abstract: To date, the effect of both fixed and time-varying individual, social, psychological, environmental, and behavioral characteristics on temporal growth trends in physical activity (PA) among younger individuals remains an under-studied topic. In this paper, we address this gap in previous work by examining how temporal growth trends in PA respond to changing social, environmental, and behavioral characteristics using a large sample of college students (N = 692) who participated in the NetHealth project at the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
(84 reference statements)
0
7
0
1
Order By: Relevance
“…The average daily step count observed in this study population was 6474 (SD 3371), which was a relatively low level of physical activity [ 42 ]. The NetHealth study conducted with 692 college students reported an average prepandemic daily step count of 11258 (SD 5874) [ 43 ]. This large difference in physical activity was likely due to pandemic procedures and norms (eg, isolation, quarantine, and public health guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…The average daily step count observed in this study population was 6474 (SD 3371), which was a relatively low level of physical activity [ 42 ]. The NetHealth study conducted with 692 college students reported an average prepandemic daily step count of 11258 (SD 5874) [ 43 ]. This large difference in physical activity was likely due to pandemic procedures and norms (eg, isolation, quarantine, and public health guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…The average daily step count observed in this study population was 6474 (SD 3371), which was a relatively low level of physical activity [42]. The NetHealth study conducted with 692 college students reported an average prepandemic daily step count of 11258 (SD 5874) [43]. This large difference in physical activity was likely due to pandemic procedures and norms (eg, isolation, quarantine, and public health guidelines).…”
Section: Comparison With Prior Workmentioning
confidence: 75%
“…These are all aspects of exercise. It has been established that daily sociability, psychological factors such as high extroversion levels, and behavioral factors such as large network size are important modulators of the physical activity implication in young populations [20]. Providing highly active participants with personalized feedback helps facilitate positive emotional responses.…”
Section: Related Workmentioning
confidence: 99%